A Case Study- Dashamoola Niruha Basti and Shamana Chikitsa in PCOS w.s.r Arthava Kshaya - Kumar M, Sharath (International Research Journal of Ayurveda & Yoga, 2022)
PCOD is one of the conditions affecting this unique capacity of woman. The disorder is probably the most common hormonal abnormality in women of reproductive age and certainly a leading cause of infertility. PCOS (polycystic ovarian syndrome) is a complex disorder comprising of anovulation, hyperandrogenism and polycystic ovaries. In Ayurveda all gynecological disorders are explained under Yonivyapad. Based on the principles of yonivyapad, PCOS can be diagnosed and treated as well. Her reports showed PCOS, right tubal block and Anovulatory cycles. She was treated with different Ayurveda treatment modalities Niruha basti (oil and decoction enema) and internal medicines like Abhraloha Aarogyavardhini and Dashamoolarishta.